High performance induction motor drive using hybrid Fuzzy-PI and PI Controllers: a Review - Saghafinia, A.; Ping, H.W.; Rahman, M.A. (Praise Worthy Prize, 2010)
Applications of fuzzy logic controller (FLC) to induction motor (IM) drives are on the rise This paper presents an overview of high performance indirect field-oriented control (IFOC) of IM drives with the focus of hybrid fuzzy with self-tuning FLC - PI controller plus PI speed controller It presents a systematic design of this controller and identifies the factors that yield robust performances for niche applications Copyright (C) 2010 Praise Worthy Prize S r l. - All rights reserved.